2014
DOI: 10.1007/s10734-014-9784-3
|View full text |Cite
|
Sign up to set email alerts
|

Who teaches academic integrity and how do they teach it?

Abstract: Who teaches academic integrity and how do they teach it?

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
55
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 128 publications
(59 citation statements)
references
References 26 publications
1
55
0
3
Order By: Relevance
“…In the literature review undertaken by Macfarlane et al (2014) the predominant focus emerging in the literature was on investigating and illustrating a perceived lack of absence of academic integrity, and in this context identified that there is a pressing need for greater understanding of academic integrity across all practice elements, including teaching. The current proactive ethos towards academic integrity is influenced not only by policy actions, such as syllabi and course outlines acknowledgement of academic integrity, ethical guidelines or codes of conduct, but also by the very capacity of academics to teach and/or influence the students' awareness and acceptance of academic integrity standards (Löfström et al 2015).…”
Section: Information Ecology At the Heart Of Academic Integritymentioning
confidence: 99%
“…In the literature review undertaken by Macfarlane et al (2014) the predominant focus emerging in the literature was on investigating and illustrating a perceived lack of absence of academic integrity, and in this context identified that there is a pressing need for greater understanding of academic integrity across all practice elements, including teaching. The current proactive ethos towards academic integrity is influenced not only by policy actions, such as syllabi and course outlines acknowledgement of academic integrity, ethical guidelines or codes of conduct, but also by the very capacity of academics to teach and/or influence the students' awareness and acceptance of academic integrity standards (Löfström et al 2015).…”
Section: Information Ecology At the Heart Of Academic Integritymentioning
confidence: 99%
“…For instance, integrity can be embedded into higher education through discussing ethical values and practices in the classroom, role modeling standards of integrity, and building students’ profession-specific ethics expertise via a well-validated ethics curriculum and assessing relevant outcomes (e.g., Bebeau and Thoma, 1998; Löfström et al, 2015). …”
Section: Discussionmentioning
confidence: 99%
“…While specificity in integrity policy is necessary, academics themselves need to understand and communicate to students what is essentially meant by misconduct (Collins and Amodeo 2005). Research in the fields of psychology and business suggests that researchers and students alike may be confused about what constitutes ethical behavior and under what conditions (e.g., collaboration versus collusion Barrett and Cox 2005;Sutton and Taylor 2011;Löfström et al 2015).…”
Section: Integrity Policymentioning
confidence: 99%